Coffee prevents fatty liver disease induced by a high-fat diet by modulating pathways of the gut–liver axis - Vitaglione, Paola; Mazzone, Giovanna; Lembo, Vincenzo; D'Argenio, Giuseppe; Rossi, Antonella; Guido, Maria; Savoia, Marcella; Salomone, Federico; Mennella, Ilario; De Filippis, Francesca; Ercolini, Danilo; Caporaso, Nicola; et al. (Journal of nutritional science (Cambridge), 2019)
Coffee consumption is inversely associated with the risk of non-alcoholic fatty liver disease (NAFLD). A gap in the literature still exists concerning the intestinal mechanisms that are involved in the protective effect of coffee consumption towards NAFLD. In this study, twenty-four C57BL/6J mice were divided into three groups each receiving a standard diet, a high-fat diet (HFD) or an HFD plus decaffeinated coffee (HFD+COFFEE) for 12 weeks. Coffee supplementation reduced HFD-induced liver macrovesicular steatosis ( P < 0·01) and serum cholesterol ( P < 0·001), alanine aminotransferase and glucose ( P < 0·05). Accordingly, liver PPAR- α ( P < 0·05) and acyl-CoA oxidase-1 ( P < 0·05) as well as duodenal ATP-binding cassette (ABC) subfamily A1 ( ABCA1 ) and subfamily G1 ( ABCG1 ) ( P < 0·05) mRNA expressions increased with coffee consumption. Compared with HFD animals, HFD+COFFEE mice had more undigested lipids in the caecal content and higher free fatty acid receptor-1 mRNA expression in the duodenum and colon. Furthermore, they showed an up-regulation of duodenal and colonic zonulin-1 ( P < 0·05), duodenal claudin ( P < 0·05) and duodenal peptide YY ( P < 0·05) mRNA as well as a higher abundance of Alcaligenaceae in the faeces ( P < 0·05). HFD+COFFEE mice had an energy intake comparable with HFD-fed mice but starting from the eighth intervention week they gained significantly less weight over time. Data altogether showed that coffee supplementation prevented HFD-induced NAFLD in mice by reducing hepatic fat deposition and metabolic derangement through modification of pathways underpinning liver fat oxidation, intestinal cholesterol efflux, energy metabolism and gut permeability. The hepatic and metabolic benefits induced by coffee were accompanied by changes in the gut microbiota.